Effectiveness of Different Configurations of Ferrocement Retrofitting for Seismic Protection of Confined Masonry: A Numerical Study - Habieb, Ahmad B.; Hidayat, Muhammad R.; Sutrisno, Wahyuniarsih; Kandymov, Nurmurat; Milani, Gabriele (Civil Engineering Journal, 2024)
A ferrocement layer, which consists of a wire mesh and cement mortar, is a popular retrofitting method for existing structural elements, particularly wall or slab panels. This paper presents a study on the effectiveness of different configurations of ferrocement for seismic retrofitting of confined masonry through finite element analysis. The masonry panel was modeled using expanded brick-unit elements, where the element was expanded in size by as much as half of the mortar thickness, and an interacting zero-thickness interface was applied to mimic the elastic-plastic and damage behavior during tension, shear, and compression. The concrete damage plasticity (CDP) model was used to model the confining reinforced concrete frame and overlay mortar in the ferrocement layer, and the reinforcing bars and wire mesh were modeled using elastic-plastic behavior. In the present numerical study, nine models were subjected to cyclic and pushover shear test simulations, considering the effects of the number of ferrocement layers and the wire mesh orientation. The volumetric ratio of the wire mesh to the masonry (ρwm) ranged from 0.48% to 1.92%, whereas the ratio of the mortar overlay to the masonry (ρmo) varies from 10.42% to 41.66%. Based on the increase in the lateral strength, the model with the largest volume of the ferrocement layer exhibited the largest increase in strength. However, the most cost-effective retrofitting configuration was presented by model DS-1-45, in which a single layer of ferrocement was applied on both sides of the wall using 45° of wire mesh orientation. The DS-1-45 model provided a lateral strength increase of more than 6 times compared to the original unreinforced model. Doi: 10.28991/CEJ-2024-010-09-02 Full Text: PDF